2003
DOI: 10.1590/s0074-02762003000100001
|View full text |Cite
|
Sign up to set email alerts
|

Should Trypanosoma cruzi be called "cruzi" complex? A review of the parasite diversity and the potential of selecting population after in Vitro culturing and mice infection

Abstract: Morpho-biological diversity of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
7

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 127 publications
(142 reference statements)
2
65
0
7
Order By: Relevance
“…In this study, results of hybridization profiles with the panel of probes did not show different T. cruzi genotypes among the species studied, which indicated that T. cruzi genotypes do not have specific associations with wild mammal species, as suggested. 11,44 Moreover, results for T. cruzi genotypes circulating in C. hircus, a recently introduced host, do not vary substantially from native hosts. These results indicate that there is no evidence for a strong host-parasite association between specific mammal hosts and T. cruzi genotypes.…”
Section: Discussionmentioning
confidence: 95%
“…In this study, results of hybridization profiles with the panel of probes did not show different T. cruzi genotypes among the species studied, which indicated that T. cruzi genotypes do not have specific associations with wild mammal species, as suggested. 11,44 Moreover, results for T. cruzi genotypes circulating in C. hircus, a recently introduced host, do not vary substantially from native hosts. These results indicate that there is no evidence for a strong host-parasite association between specific mammal hosts and T. cruzi genotypes.…”
Section: Discussionmentioning
confidence: 95%
“…However, as the isolation of the parasites in cultures or mice could lead to strain selection, only direct characterization from insects and mammalian samples allow strains to be typed without bias. 16 On this basis, and given the high sensitivity of kinetoplastid minicircle amplification by polymerase chain reaction (PCR), the polymorphism of minicircle hypervariable regions (mHVRs) has been used in many studies for the direct molecular characterization of parasitic populations from biological samples. 8,[17][18][19][20][21][22] Beyond the high variability of mHVR, the comparison of several minicircle regions within and among strains, has allowed identification of some sequences more represented in certain sublineages.…”
Section: Introductionmentioning
confidence: 99%
“…T. cruzi I is linked to the sylvatic cycle and human disease in Central America and the Andean countries, and T. cruzi II in the Southern Cone countries is related to the domestic cycle and produces major infections and morbidity in humans. 45,46 Because most immigrants in the United States are from Mexico and Central America, it may be possible that the T. cruzi I lineage infecting them is less able to produce congenital T. cruzi infection than the T. cruzi II lineage, which is more common in countries from the Southern cone, where most cases of congenital T. cruzi infection have been described. 1,3,4,[7][8][9][10][11][12][13][14][15][16][17][18][19][20] In addition, because neither the Hispanic pregnant women nor their newborns are screened for Chagas disease, it may also be possible that inexperienced health personnel miss the asymptomatic or oligosymptomatic cases and the symptomatic cases.…”
Section: Resultsmentioning
confidence: 99%